Phthalocyanines including 2-mercaptobenzimidazole analogs: Synthesis, spectroscopic characteristics, quantum-chemical studies on the relationship between electronic and antioxidant properties - Yakan, Hasan; Çavuş, M. Serdar; Güzel, Emre; Arslan, Barış S.; Bakır, Temelkan; Muğlu, Halit (Elsevier BV, 2020)
Abstract In this study, peripherally tetra 2-mercaptobenzimidazole group substituted cobalt and indium phthalocyanine complexes (2 and 3) were prepared from 4-(benzo[d]imidazole-2-ylthio)phthalonitrile (1) for the first time. Antioxidant behaviors and theoretical calculations of benzimidazole-substituted metallophthalocyanines are presented. The structures of these compounds were determined by the spectroscopic methods (IR, 1H NMR, UV–Vis and mass spectroscopies) and elemental analysis. Antioxidant activities of the compounds (1–3) were measured using 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. Antioxidant activity was followed by 1 > 3 > 2 > Trolox. In addition, density functional theory (DFT) calculations were carried out to determine the stable electronic structure, charge density distributions, FMO energy eigenvalues, and electronegativity of the ligand (1) and complexes (2 and 3). NBO and QTAIM analysis were performed to investigate the relationship between the electronic properties and antioxidant activity of the compounds.
Keywords: Chemistry; QTAIM; Antioxidant activity; Phthalocyanine; Spectroscopic methods; DFT